Relationship between Prostate Volume and International Prostate Symptom Score (IPSS) Degree of Tamed Prostate Enlargement on Transabdominal Ultrasonography (TAUS) and Transrectal Ultrasonography (TRUS) Examination - Eriawan Agung Nugroho; Abu Azhar; Ezra Endria Gunadi (Biomedical Journal of Indonesia, 2021)
Introduction: IPSS is the gold standard in measuring clinical symptoms of BPH.1Prostate volume has been said to have a close relationship with the development of BPH.9 The aim of this study was to determine the relationship between prostate volume as measured by transabdominal ultrasonography (TAUS) and transrectal (TRUS) to the degree of IPSS. Methods: An analytic observational study with a cross sectional design was carried out on 303 BPH patients at the General Hospital of Kariadi Hospital, Semarang. The data obtained from the TAUS, TRUS and IPSS prostate volume were obtained from medical records for the period 2015 - 2020. The data were then analyzed by using the chi square test. Results: Patients with BPH have a TAUS prostate volume in classification I of 0 people 0%, classification II of 16 people (5.3%), classification III of 96 people (31.7%), classification IV of 102 people (33.7%) and classification V of 89 people (29.4%). While TRUS in classification I was 0% (0 people), classification II was 11 people (3.6%), classification III was 92 people (30.4%), classification IV was 110 people (36.3%) and classification V of 90 people (29.7%). IPSS obtained severe IPSS degrees, namely 192 people (63.4%), moderate degrees of 111 people (36.6%), and mild degrees 0% (0 people). The results of the Chi Square test obtained a p-value of 0.000 (p <0.05), indicating that there was a significant relationship between prostate volume, whether examined by transabdominal or transrectal ultrasound, and the degree of IPSS. The correlation coefficient r = 0.925 indicates a very strong relationship between prostate volume as measured by both transabdominal and transrectal ultrasound with the degree of IPSS, a positive result shows that the increase in prostate volume, the degree of IPSS will also increase. Conclusion: There is a significant relationship between prostate volume as measured by both TAUS and TRUS and the degree of IPSS.